Evaluation of the effects of PHAST training and community health interventions on the hygiene behaviour of children and women to prevent diarrhoeal diseases- in the Locality of Rashad/ South Kordofan/ Republic of Sudan - Annett Weidner (2010)
Access to drinking water and improved sanitation are a fundamental need for health of all people. Diarrhoea due to infection is widespread throughout the developing world. It is estimated that 90.0% of all cases of diarrhoea can be attributed to three major causes: inadequate sanitation, poor hygiene and unclean water. Each year approximately 2.2 million people die from diarrhoeal diseases worldwide, 90.0% are children under 5 years of age. (WHO, 2000)